Social Responsibility and Ethical Marketing at PT Karya Tetangga Tuku (Kopi Tuku) - Ayu Anix Matunisa; Defi Herfiana; Arfiani Yulianti Fiyul (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of business ethics and Corporate Social Responsibility (CSR) at PT Karya Tetangga Tuku (Kopi Tuku) within the highly competitive local coffee industry. A qualitative descriptive approach was employed using in-depth interviews, non-participant observation, and documentation techniques. The findings reveal that Kopi Tuku consistently applies ethical marketing principles based on honesty, transparency, and simplicity in marketing communication, customer service, and pricing practices. Furthermore, the company’s CSR implementation encompasses economic, social, ethical, and environmental dimensions through the empowerment of local coffee farmers, human resource development, and environmentally friendly practices. The integration of ethical marketing and CSR has positively influenced consumer trust, customer loyalty, brand image, and business sustainability. This study concludes that the alignment of business ethics and CSR serves not only as a moral obligation but also as a strategic approach to achieving long-term competitiveness and corporate legitimacy.